(untitled) (CIPEEX, 2025)
Silver (Ag) has a long history of use in technology and medicine, with the advent of silver nanoparticles (AgNPs) for applications in electronics and nanomedicine driven by their unique optical and electronic properties. However, the high reactivity of AgNPs, due to their large surface area, can generate reactive oxygen species (ROS), which raises serious safety concerns for biomedical applications. This work proposes a theoretical study using computational quantum chemistry through Density Functional Theory (DFT), with the B3LYP functional and the 6-31G and 6-311G(d,p) basis sets, to investigate the absorption and emission spectral behavior of silver in three solvent media: aqueous, ethanol, and methanol. The objective is to understand how interactions with these solvents affect silver’s electronic properties, providing fundamental insights for developing new, safer, and tunable drugs and technologies. Based on previous studies, it is expected that the absorption spectra of silver will be significantly influenced by its charge state and cluster size, with neutral clusters showing a spectral shift to lower energies compared to charged ones. The oscillator strength for neutral clusters is generally greater than for charged ones, which may be related to the increased luminescence intensity observed in experiments when charged silver clusters are converted to neutral ones. The simulations are anticipated to show a similar effect for the solvents, meaning the modulation of absorption and emission peaks, which is crucial for engineering photonic materials like white lightemitting diodes (LEDs). We conclude that the ability to predict silver’s behavior in different media is essential for optimizing its spectral properties, with a view to biomedical applications such as biosensors and photodynamic therapies, as well as other emerging technologies.